At the foot of Mount Olympus: A theory on myth - Schutte, Flip (HTS teologiese studies, 2006)
A cult normally develops around myths and rituals. In this article myth as phenomenon will be investigated. Different types and categories of myths will be listed, while research done in the past on myths will also be dealt with. Furthermore, the issue of ritual accompanying the myth will be briefly discussed. This article wants to promote the notion that one does not need any particular worldview, be it mythological, orthodox, fundamentalistic, or biblisistic, to use, understand, and appreciate myths. Even in a postmodern world the value of myths can be appreciated.